Pengembangan Arsitektur Data Sistem Informasi Sekolah - Putra, Rizqi Ari; Alauddin, Muhammad Fahmi; Alam, Islam Nur; Yaqin, Muhammad Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The purpose of this study is to design a School Information System database architecture based on National School Standards. National School Standards are used as a reference in determining business processes in a school, especially elementary and midle-high school. These processes then describe the entity and its attributes. The database used is a Relational Database so that entities and attributes are drawn as a table that has relationships between entities. To model relationships between entities, use Entity Relational Diagrams. The results of this study are the realization of database architecture with national school standards. This database architecture design is expected to be a reference in building School Information Systems that are in accordance with National School Standards.